2001
DOI: 10.1126/science.1059042
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Phospholipase Cδ4 for the Zona Pellucida-Induced Acrosome Reaction

Abstract: Several phospholipase C (PLC) isoforms have been found in male and female mammalian gametes, and splicing isoforms of PLCdelta4 are predominantly expressed in testis. Here we report that male mice in which the PLCdelta4 gene had been disrupted either produced few small litters or were sterile. In vitro fertilization studies showed that insemination with PLCdelta4-/- sperm resulted in significantly fewer eggs becoming activated and that the calcium transients associated with fertilization were absent or delayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(117 citation statements)
references
References 19 publications
2
114
0
1
Order By: Relevance
“…In support of this notion, a targeted gene disruption study revealed that PLCd4-null male mice were infertile, and in vitro fertilization experiments showed that, despite exhibiting normal morphology and motility, PLCd4 deficient sperm were unable to fertilize efficiently (Fukami et al, 2001). However, additional ICSI studies showed that mutant sperm were as capable of triggering [Ca 2+ ] i oscillations as wild type sperm (Fukami et al, 2001). Furthermore, injection of recombinant PLCd4 protein failed to initiate oscillations in mouse eggs (Fukami et al, 2001, unpublished observations).…”
Section: Plcd4mentioning
confidence: 96%
See 2 more Smart Citations
“…In support of this notion, a targeted gene disruption study revealed that PLCd4-null male mice were infertile, and in vitro fertilization experiments showed that, despite exhibiting normal morphology and motility, PLCd4 deficient sperm were unable to fertilize efficiently (Fukami et al, 2001). However, additional ICSI studies showed that mutant sperm were as capable of triggering [Ca 2+ ] i oscillations as wild type sperm (Fukami et al, 2001). Furthermore, injection of recombinant PLCd4 protein failed to initiate oscillations in mouse eggs (Fukami et al, 2001, unpublished observations).…”
Section: Plcd4mentioning
confidence: 96%
“…Moreover, PLCs are well known to be involved in cell growth, differentiation, and cytoskeletal organization (Divecha and Irvine, 1995;Rhee, 2001). To date, 12 PLC isozymes (b1-4, c1-2, d1-4, e, f) have been identified, and expression of PLCb1, b3, c1, and c2 has been noted in mouse eggs (Dupont et al, 1996;Mehlmann et al, 1998;Wang et al, 1998), whereas expression of b1-3, c1-2, d2, d4, and f has been detected in sperm Fukami et al, 2001;Wu et al, 2001b;Parrington et al, 2002;Saunders et al, 2002). Importantly, discriminating whether a PLC(s) from eggs or sperm, or a combination of PLCs from both gametes, plays a role in mammalian fertilization has proven an elusive task.…”
Section: Egg-or Sperm-derived Plcs?mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this idea, T. cruzi contains a PLC-␦ isoform (41) and PLC-␦ candidate sequences are present in the Plasmodium falciparum and Plasmodium vivax genomes (42). While not conventionally associated with Ca 2ϩ signaling, PLC-␦ has recently been linked to Ca 2ϩ transients associated with fertilization in mice (43). Thus, it is possible that PLC-␦ plays an important role in protozoan calcium regulation.…”
Section: Fig 3 Ethanol Increases T Gondii Ipmentioning
confidence: 99%
“…1 There are several isoforms of PLC in the spermatozoa (10,11). PLC␦4, in particular, has been implicated in the early events of the acrosome reaction (12). Active PLC would produce inositol 1,4,5-trisphosphate (IP 3 ) that would open IP 3 -sensitive calcium channels in the membrane of intracellular stores.…”
mentioning
confidence: 99%